Authenticities: A Semiotic Exploration - Fenigsen, Janina; Wilce, James (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2012)
Charles Taylor has called ours an “Age of Authenticity”, and authenticity is a popular object of scholarly examination, not least in anthropology. A considerable number of scholars have even proposed models for multiple “authenticities”. None, however, has brought a modified Peircean theoretical tool-kit together with ethnographic evidence that “the natives know” that there are many authenticities. This article seeks to fill that gap. Working with Peirce’s model of the sign and with postmodern theories of originals and replicas, we draw on Wilce’s Finnish fieldwork to analyze what we consider clear evidence of four authenticities arising in recent debates surrounding traditional Karelian lament and particularly highly organized attempts in Finland to “revive” the practice. We call performances arising out of the revival “neolaments”. We treat authenticities as strictly relational, metasemiotic, and ideological phenomena. Authenticities that appear salient to actors on the revivalist scene may involve the following relationships : that between any neolament performance and any particular Karelian lament performances, with the question being whether the former is adequately “traditional” (i.e. relationship between replica and original); between a particular lament performance and the generic essence of that which makes lament a lament (i.e. token and type); between a lament performance and emotion – a relationship ideologically construed as “expressive” (i.e. sign and object); and finally, a relationship between some sort of dynamic interpretant of particular old Karelian laments (lament1) and new dynamic interpretants generated in and through new lament performances (lament2 or habitual participation in such performance) that in some way replicates the old dynamical interpretant (interpretant1 and interpretant2).